PENGARUH KUALITAS PRODUK DAN STRATEGI ATM TERHADAP KINERJA PEMASARAN DENGAN DAYA TARIK PRODUK SEBAGAI VARIABEL INTERVENING (Studi pada industri knalpot di Kab .Purbalingga ) - Endang Rusdianti; Paulus Wardoyo; Sri Purwantini (Universitas Semarang, 2019)
This study aims to analyze the marketing performance of IKM Knalpot in Purbalingga Regency. The specific target of the research results is to analyze whether product quality and ATM strategy affect the attractiveness of the product and whether through the attraction of this product can be achieved the goal of increasing marketing. The method used is Regression technique using Smart PLs2. The type of data used is primary data obtained by using a questionnaire method on variable product quality, ATM strategy, product attractiveness and marketing performance. The respondents were 75 mufflers / mufflers in Banjarnegara. The results showed that product quality and ATM strategy had an effect on the attractiveness of the product. To improve marketing performance, intervening variables are used, namely the attractiveness of the product. And the results show that the attractiveness of the product can act as an intervening variable and can further improve marketing performance.